Competency Assessment for Entry-level Sport Ticket Sales Professionals - David Pierce; Richard Irwin (Journal of Applied Sports Management, 2016)
With the emergence of outbound sales philosophies taking hold in sport organizations, sales managers are seeking talent to fill sales positions with candidates launching their careers in the sport industry. However, observers have noted that the infusion of sport ticket sales personnel has not been accompanied by an appropriate professional development and evaluation protocol, which has contributed to high turnover rates. As sport management education programs modernize their curriculum to meet industry needs and sales managers attempt to reduce turnover, a better understanding of the competencies required of entry-level sport ticket sales professionals is required. The purpose of this research was to identify the competencies required for success in an entry-level sport ticket sales position and the extent to which sales managers find it difficult to train salespeople on those competencies. Nineteen sport sales managers served as expert panelists on a study that employed the Delphi method. The result of the study is a 40-item competency model comprised of the following eight global competency areas: knowledge and skill development, relationship building, communication skills, opening the sale, consultative or adaptive sales, closing, maximizing each call, and service and education. Implications for sales managers, human resource managers, sport sales educators, and academic scholarship in sport sales are discussed.
Keywords: sales; sales management; sales competency; sales effectiveness; sport sales